Myricetin protects mice against colitis by activating aryl hydrocarbon receptor signaling pathway - Tao Xu; Xinyan Qu; Yue Song; Mengxiong Luo; Yuhan Jia; Jia Li; Qingjun Li (Food & Nutrition Research)
Objective: Myricetin is a bioactive compound in many edible plants. We have previously demonstrated that myricetin could significantly protect mice against colitis by regulating Treg/Th17 balance, while underlying mechanism remains unclear. The current study aimed to unravel the potential regulating mechanism of myricetin. Methods: The concentrations of 22 amino acids in colon were determined using HPLC-MS/MS and principal component analysis (PCA) was performed on the data. MetaboAnalyst was used to detect potential biological pathway influenced by myricetin. The results were further verified using qPCR, molecular docking method, and AhR inhibitor. Results: Studies had found that the biosynthesis of phenylalanine, tyrosine, and tryptophan; phenylalanine metabolism; and histidine metabolism were the most important pathways related to myricetin. Therefore, the aryl hydrocarbon receptor (AhR), which is closely related to the metabolism of tryptophan, phenylalanine, and tyrosine, was postulated to be the underlying signaling pathways. Furthermore, administration of myricet in significantly increased the relative expressions of CYP1A1 and CYP1B1, whereas AhR inhibitor abolished the amelioration of myricetin on DSS-induced colitis. Moreover, AhR inhibitor weakened the regulatory effect of myricetin on Treg/Th17 balance. Furthermore, the results obtained by the molecular docking method speculated that myricetin could bind to AhR as a ligand and activate AhR. Conclusion: The results suggested that myricetin could exert its protection against dextran sulfate sodium (DSS)-induced colitis by activating AhR signaling pathway.